Na,K-ATPase α4 isoform is essential for sperm fertility - Jimenez, Tamara (National Academy of Sciences, 2011)
Regulation of ion balance in spermatozoa has been shown to be essential for sperm motility and fertility. Control of intracellular ion levels requires the function of distinct ion-transport mechanisms at the cell plasma membrane. Active Na(+) and K(+) exchange in sperm is under the control of the Na,K-ATPase. Two molecular variants of the catalytic subunit of the Na,K-ATPase, α1 and α4, coexist in sperm. These isoforms exhibit different biochemical properties; however, their function in sperm fertility is unknown. In this work, we show that Na,K-ATPase α4 is essential for sperm fertility. Knockout male mice lacking α4 are completely sterile and spermatozoa from these mice are unable of fertilizing eggs in vitro. Furthermore, α4 deletion results in severe reduction in sperm motility and hyperactivation typical of sperm capacitation. In addition, absence of α4 causes a characteristic bend in the sperm flagellum, indicative of abnormal sperm ion regulation. Accordingly, α4-null sperm present increased intracellular Na(+) and cell plasma membrane depolarization. These results are unique in demonstrating the absolute requirement of α4 for sperm fertility. Moreover, the inability of α1 to compensate for α4 suggests that α4 is the Na,K-ATPase-α isoform directly involved in sperm fertility. Our findings show α4 as an attractive target for male contraception and open the possibility for the potential use of this Na,K-ATPase isoform as a biomarker for male fertility.